MRI visualisation of moisture ingress into porous tissue of decayed teeth - Węglarz, Władysław P.; Tanasiewicz, Marta M.; Gruwel, Marco L. H.; Tomanek, Boguslaw (Diffusion Fundamentals, 2009)
MR imaging of moisture ingression into porous tissue of decayed teeth in vitro with resolution of 30´120´180 μm3 was obtained using a 4.7 T research MRI scanner and a spinecho pulse sequence. High resolution images allowed the visualisation of the 3D structure of tooth pores and the estimation of their size and extent. Using a Single Point Imaging method, images of the mineralized tissue of teeth were obtained.